Prognostic relevance of the Ki-67 proliferation index in patients with mantle cell lymphoma - Jeong, Tae-Dong; Chi, Hyun-Sook; Kim, Min-Sun; Jang, Seongsoo; Park, Chan-Jeoung; Huh, Joo Ryung (Blood research, 2016)
A high Ki-67 proliferation index (PI) in neoplastic cells is associated with poor survival in mantle cell lymphoma (MCL). We aimed to determine the cut-off values for the Ki-67 PI as a prognostic factor in MCL according to bone marrow findings. Immunohistochemical (IHC) staining for Ki-67 was performed on formalin-fixed paraffin-embedded biopsy tissues from 56 patients with MCL. Patients were grouped based on their Ki-67 PI values. Survival analyses were carried out and the cut-off value for the Ki-67 PI was determined. Of the 56 patients, 39 (69.6%) showed bone marrow involvement of MCL; 21 of these patients had leukemic manifestations at the time of diagnosis. The results of the Ki-67 IHC staining were as follows: ≤10% in 22 patients, 11-20% in 14 patients, 21-30% in 3 patients, 31-40% in 4 patients, 41-50% in 4 patients, and >50% in 9 patients. A cut-off value of 20% revealed significantly different survival rates with mean survival times of 69.8 months (Ki-67 PI≤20%) and 47.9 months (Ki-67 PI>20%), irrespective of bone marrow findings (P=0.034). Clinical outcomes did not differ, regardless of bone marrow findings. However, in cases with bone marrow involvement, the Ki-67 cut-off value of 30% for overall survival was required to yield statistical significance (P=0.033). The 20% cut-off value for the Ki-67 PI was clinically meaningful, regardless of bone marrow involvement of MCL. For patients with bone marrow involvement, the statistically significant cut-off value increased to 30%.